Factors Affecting the Success of Data Driven Marketing - Nisula, Reetta (My University, 2019)
Due to digitalization, there is nowadays a voluminous amount of data involved in running a business, and data about the customers is flowing to the organizations from multiple different sources. Solely possessing vast amounts of data is not creating value, and often, organizations struggle to transform this data into actions and create a competitive advantage of it. To contribute to this managerial challenge, the purpose of this study is to identify the key factors that help companies to succeed in data-driven marketing. In this study, data-driven marketing refers to the concept of acquiring, analyzing, and applying all relevant information about customers to optimize marketing processes. Marketing processes are all business processes participating in customer value creation, and therefore, data-driven marketing is an operating model that affects the whole organization. Data-driven marketing is a complex concept without an established definition. Thus, this study is conducted as an exploratory field study. Data is collected by interviewing marketing and data analytics consultants, along with practicing managers working in companies that implement a data-driven marketing approach. The main theoretical contribution of this study is to identify the key factors that help companies to succeed in data driven marketing. This study supports the existing understanding that senior management factors are the most crucial ones for data-driven marketing success. The organizational change towards data-driven marketing requires that senior management supports the change and allocates enough resources for the matter. Senior management should see data-driven marketing as a strategic tool by which the organization's market-oriented strategy can be implemented into practice. In addition to the senior management factors, this study also highlights the need for clearly defined goals and performance metrics. Data-driven marketing is about the ongoing optimization of different marketing processes with market intelligence. The first step in process optimization should be to understand what the primary purpose of the process is and what should be the outcome of it. The study contributes to the existing understanding by emphasizing the importance of the factors related to the organization's internal dynamics and culture. The starting point for data-driven marketing success should be to change the way the organization sees marketing processes and to motivate decision-makers to use the acquired information - not fixing the problems regarding the data and information systems. Moreover, the findings indicate that for many times, obstacles with data and information systems reflect the organization's structure and dynamics.